PEDAGOGICAL FOUNDATIONS OF TRAINING PRIMARY SCHOOL TEACHERS - Saparova Zaynab Ulug‘bek qizi (Bright Mind Publishing, 2025)
This article examines the pedagogical foundations of training primary school teachers. It discusses the teacher’s professional competence, pedagogical skills, innovative approaches, educational activities, and the significance of teaching practice. The paper also analyzes the role and responsibility of primary school teachers in the modern education system.
Keywords: Primary education, pedagogy, teacher training, professional competence, pedagogical skills, innovative education, upbringing.